Hypomenorrhea in Adolescents and Youths: Normal Variant or Menstrual Disorder? Revision of Literature and Personal Experience : Hypomenorrhea in Adolescents and Youths - De Sanctis, Vincenzo; Soliman , Ashraf T; Tzoulis, Ploutarchos; Daar, Shahina; Di Maio , Salvatore; Millimaggi, Giuseppe; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2022)
Abstract. Menstrual health affects a large number of women throughout reproductive life since adolescence. Knowledge of the duration and variation of the menstrual cycle is necessary for patient education and to identify deviations from normal to guide clinical evaluation. The average duration of menstrual flow is between 4 to 6 days, with anormal range from 2 up to 8 days ; the mean blood loss per menstrual cycle is 25- 30 mL. In general, descriptive data falling outside the normal range are considered to be indicative of menstrual disorders. Although the American Academy of Pediatrics and American College of Obstetricians and Gynecologists advocate for clinicians to consider the menstrual cycle as a vital sign in adolescents, the identification of subjects with hypomenorrhea is neither well defined nor routinely practiced. In this paper we have summarized the published prevalence of hypomenorrhea (lighter and/or shorter menstrual bleeding) in adolescents and youths in different countries and report the personal experience in four adolescents.